Keputusan Investasi dan Keputusan Pendanaan Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Natalia Margaretta Siringo-Ringo; Darmae Nasir; Christina Fransiska; Sri Yuni; M. Ichsan Diarsyad; Iwan Christian (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to provide an empirical explanation of the Influence of Investment Decision and Funding Decisions on Firm Value with Firm Size as a Moderating Variable in Consumer Goods Companies. The research method used in this study is a quantitative descriptive research approach. The samples in this study are 25 Consumer Goods Companies that are listed on the Indonesia Stock Exchange for 2019-2021. The date werw then analyzed using multiple regression analysis and moderated regression analysis (MRA). By using SPSS 25 software. The result showed that the investment decision variable had a negative and significant effect on firm value, while the funding decision variable had a negative and significant effect on firm value. Then fpr the company size variable it is able to strengthen the investment decision variables and funding decisions on firm value. The company is expected to provide benefits for the company’s management to increase the value of the company in the future. Investors are expected to minimize risk in investing. For future researchers, it is hoped that they can add other variables that might better predict the value relevance of financial statements